Bi‐MOF Modulating MnO2 Deposition Enables Ultra‐Stable Cathode‐Free Aqueous Zinc‐Ion Batteries. Issue 17 (22nd January 2023) - Gou, Lei; Li, Junru; Liang, Kai; Zhao, Shaopan; Li, Donglin; Fan, Xiaoyong
Abstract: The Mn‐based materials are considered as the most promising cathodes for zinc‐ion batteries (ZIBs) due to their inherent advantages of safety, sustainability and high energy density, however suffer from poor cyclability caused by gradual Mn 2+ dissolution and irreversible structural transformation. The mainstream solution is pre‐adding Mn 2+ into the electrolyte, nevertheless faces the challenge of irreversible Mn 2+ consumption results from the MnO2 electrodeposition reaction (Mn 2+  → MnO2 ). This work proposes a "MOFs as the electrodeposition surface" strategy, rather than blocking it. The bismuth (III) pyridine‐3, 5‐dicarboxylate (Bi‐PYDC) is selected as the typical electrodeposition surface to regulate the deposition reaction from Mn 2+ to MnO2 . Because of the unique less hydrophilic and manganophilic nature of Bi‐PYDC for Mn 2+, a moderate MnO2 deposition rate is achieved, preventing the electrolyte from rapidly exhausting Mn 2+ . Simultaneously, the intrinsic stability of deposited R‐MnO2 is enhanced by the slowly released Bi 3+ from Bi‐PYDC reservoir. Furthermore, Bi‐PYDC shows the ability to accommodate H + insertion/extraction. Benefiting from these merits, the cathode‐free ZIB using Bi‐PYDC as the electrodeposition surface for MnO2 shows an outstanding cycle lifespan of more than 10 000 cycles at 1 mA cm ‐2 . This electrode design may stimulate a new pathway for developing cathode free long‐life rechargeable ZIBs. Abstract : A "MOFs as the electrodeposition surface" strategy is proposed to regulate the deposition reaction from Mn 2+  to MnO2, and a cathode free Zn‐ion battery with a long cycle life and high capacity is fabricated by the judicious selection of Bi‐PYDC ( PYDC = pyridine‐3, 5‐dicarboxylate) surface due to the three benifits it provides.